Students’ Perception of Using Animation Video in Teaching Writing Narrative Text - Pratiwi, Firda; Suharsih, Siti; Fargianti, Yusti (Journal of Linguistics, Literacy, and Pedagogy, 2022)
The objectives of this research are to reveal the students’ perception of using animation video in teaching writing narrative text and also to find out the advantages and disadvantages of animation video. This research was conducted at MA Ibad Ar-Rahman Islamic Boarding School. The writer has conducted a qualitative method by using case study research design. The tools of data collection are open-ended questionnaire, semi-structured interview, and documentation. It was found that the students have a positive perception on using animation video. The writer used animation video as media in teaching writing narrative text. The students agree that animation video can help them in learning writing narrative text, 95% students give positive perception and 5% students give negative perception. The utilization of animation video can make the students feel happy because they do not need to imagine the story of the narrative text. However, if the duration of video is too long, it makes the students feel bored.